2013
DOI: 10.1364/oe.21.011115
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid analysis method for plasmonic enhanced terahertz photomixer sources

Abstract: A hybrid analysis of a continuous-wave terahertz photomixer source structure with plasmonic nano-grating electrodes is presented. Using the hybrid analysis, the enhancement of the optical power absorption due to the presence of the one-dimensional metallic nano-grating is investigated by defining an absorption enhancement factor. We show that the proposed absorption enhancement factor can be used as a design tool, whose maximization provides the optimum geometrical parameters of the nano-grating. Based on drif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Knowing the amplitudes of the optical generation rate and the electric field, throughout the LTG-GaAs, we can readily define the photomixer efficiency, in a similar manner as in [23]…”
Section: Cw Operation Of Thz Photomixer Emittersmentioning
confidence: 99%
“…Knowing the amplitudes of the optical generation rate and the electric field, throughout the LTG-GaAs, we can readily define the photomixer efficiency, in a similar manner as in [23]…”
Section: Cw Operation Of Thz Photomixer Emittersmentioning
confidence: 99%
“…20 Recently, nanoplasmonic structures have been incorporated on the PCA to improve the efficiency. [21][22][23][24][25] In a research, Berry et al have incorporated a plasmonic grating to the 3 Â 3 array of logarithmic spiral antennas fabricated on a LT-GaAs layer. 26 They showed that nanoplasmonic resonance at the PCA gap results in high absorption of laser pulse in the photosensitive layer.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, nanoplasmonic structures have been investigated to enhance the performance of THz detectors [17][18][19]. The main advantage of the nanoplasmonic structure for detection is to create a fast sweep out time, and thereby allow for the usage of a low-cost high-mobility long carrier lifetime substrate like semi-insulating GaAs [18,[20][21][22], as opposed to other less common substrates with short carrier lifetimes (such as low-temperature GaAs or GaBiAs) [23][24][25][26][27][28][29][30][31]. For pulsed THz sources, however, the carrier lifetime is not a limiting factor [32], yet nanoplasmonic structures can still provide an advantage, as we will investigate in this work.…”
Section: Introductionmentioning
confidence: 99%